Second Language Learning in the Technology-mediated Environments (Asian Education Studies, 2018)
Digital technologies are transforming formal educational practices that extend across space and time, blurring the traditional boundaries of learning in school and out of school. Multimedia software as well as most online materials delivered via combination of different media caters to learners with different cognitive styles. Technology-enhanced learning promotes active and ubiquitous learning, location-based learning, and the generation of learning communities. L2 learners with mobile devices have the advantage of interacting with peers anytime and anywhere.